Petrology of the metamorphic rocks (gravels) from Bhajanpur area in Panchagarh District, Bangladesh (Journal of Life and Earth Science, 2011)
The present study deals with petrology of the detrital gravelly rocks from Bhajanpur area, Panchagarh, Bangladesh. The results of detailed petrography of gravelly rocks indicate the presence of quartz (monocrystalline and polycrystalline quartz), K-feldspar, plagioclase, chlorite, muscovite and biotite as major mineralogical compositions. Other minor minerals are garnet, kyanite, graphite and opaque minerals. Based on definitive mineral assemblages, blueschist and greenschist facies sequences are recognized. Correspondingly, index minerals provide chlorite zone, biotite zone, garnet zone, kyanite zone, and graphite zone. The P-T conditions of the studied rocks demonstrate the possible temperature ranges 300-550°C and pressure ranges 2-10 kbar. Most common varieties of metamorphic rocks in the study area are garnet mica schist, chlorite schist, gneiss and few quartzites. Characteristics of garnet mica schist and chlorite schist are equivalent with the lesser Himalayan metamorphic rock sequence in Sikkim area, whereas gneiss from Bhajanpur area has similar precursor as Darjeeling gneiss. Therefore, the sources of detrital metamorphic rocks in Bhajanpur area obviously come from the lesser Himalayan sequence in Sikkim and Darjeeling areas, India. Key words: Petrology; metamorphic rocks; gravels; P-T conditions; Panchagarh; lesser Himalayan sequence DOI: 10.3329/jles.v5i0.7357 J. Life Earth Sci., Vol. 5: 91-96, 2010